Historical Subtitling in the Chinese Context. A Case Study of Archaisms - Yuan, Yilei (Transletters. International Journal of Translation and Interpreting, 2019)
This paper explores historical subtitling in the Chinese context with a case study on archaisms. Dialogue with obsolete elements is common in Chinese films that are set in ancient times. This study is comprised of three of Zhang Yimou’s films. His historical films often contain an obsolete speech register, a major feature of which is archaisms. The archaisms are classified into nouns, idioms, adverbs and four-character phrases. This paper will investigate how archaisms contribute to the demonstration of history in film productions, how they are translated into English, and will also briefly mention how history is manifested through visuality.